PVA/pectin composite hydrogels inducing osteogenesis for bone regeneration. (December 2022) - Hu, Ziwei; Cheng, Jianwen; Xu, Sheng; Cheng, Xiaojing; Zhao, Jinmin; Kenny Low, Zhi Wei; Chee, Pei Lin; Lu, Zhenhui; Zheng, Li; Kai, Dan
Abstract: Hydrogels composed from biomolecules have gained great interests as biomaterials for tissue engineering. However, their poor mechanical properties limit their application potential. Here, we synthesized a series of tough composite hydrogels from poly (vinyl alcohol) (PVA) and pectin for bone tissue engineering. With a balance of scaffold stiffness and pore size, PVA-Pec-10 hydrogel enhanced adhesion and proliferation of osteoblasts. The hydrogel significantly promoted osteogenesis in vitro by improving the alkaline phosphates (ALP) activity and calcium biomineralization, as well as upregulating the expressions of osteoblastic genes. The composite hydrogel also accelerated the bone healing process in vivo after transplantation into the femoral defect. Additionally, our study demonstrated that pectin and its Ca 2+ crosslinking network play a crucial role of inducing osteogenesis through regulating the Ca 2+ /CaMKII and BMP-SMAD1/5 signaling. The optimized structure composition and multifunctional properties make PVA-Pec hydrogel highly promising to serve as a candidate for bone tissue regeneration. Graphical abstract: Image 1 Highlights: Recoverable PVA-Pec hydrogel is prepared by the freezing-thawing process. PVA-Pec-10 hydrogel display well attachment and osteogenesis capacity. PVA-Pecl-10 hydrogel enhanced osteogenesis by Ca 2+ /CaMKII and BMP-SMAD1/5 signaling.